Agriproteomics of bread wheat: comparative proteomics and network analyses of grain size variation - Dawkar, Vishal V.; Dholakia, Bhushan B.; Gupta, Vidya S. (OMICS-A Journal Of Integrative Biology, 2015)
Agriproteomics signifies the merging of agriculture research and proteomics systems science and is impacting plant research and societal development. Wheat is a frequently consumed foodstuff, has highly variable grain size that in effect contributes to wheat grain yield and the end-product quality. Very limited information is available on molecular basis of grain size due to complex multifactorial nature of this trait. Here, using liquid chromatography-mass spectrometry, we investigated the proteomics profiles from grains of wheat genotypes, Rye selection 111 (RS111) and Chinese spring (CS), which differ in their size. Significant differences in protein expression were found, including 33 proteins uniquely present in RS111 and 32 only in CS, while 54 proteins were expressed from both genotypes. Among differentially expressed proteins, 22 were upregulated, while 21 proteins were downregulated in RS111 compared to CS. Functional classification revealed their role in energy metabolism, seed storage, stress tolerance and transcription. Further, protein interactive network analysis was performed to predict the targets of identified proteins. Significantly different interactions patterns were observed between these genotypes with detection of proteins such as Cyp450, Sus2, and WRKY that could potentially affect seed size. The present study illustrates the potentials of agriproteomics as a veritable new frontier of plant omics research.